2020
DOI: 10.26803/ijlter.19.11.13
|View full text |Cite
|
Sign up to set email alerts
|

Shadow Education in Indonesia: Is It Relevant to Students’ Critical Thinking Skills in Chemistry Learning?

Abstract: Private tutoring, also known as shadow education (SE), is significant in the view of Indonesian society. It attains public reliance on children’s success at school. Although SE seems to be promising to elevate students’ achievements in school, this still needs to be proven. With the development of 21st-century skills, can SE make itself worthy of being a part of proper supplementary education? This research aims to reveal how relevant SE is to develop students’ 21st-century skills, especially critical thinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Positive feedback from students indicated that this approach was successful in achieving the desired goals. (Kawedhar et al, 2020) This study aims to uncover how relevant shadow education is for developing students' 21st century skills, especially critical thinking skills.…”
Section: Resultsmentioning
confidence: 99%
“…Positive feedback from students indicated that this approach was successful in achieving the desired goals. (Kawedhar et al, 2020) This study aims to uncover how relevant shadow education is for developing students' 21st century skills, especially critical thinking skills.…”
Section: Resultsmentioning
confidence: 99%
“…Students with excellent critical thinking skills will be better equipped for a future full of challenges and opportunities. Private tutoring neglects the essence of students’ actual learning ( Kawedhar et al, 2020 , pp. 225–226) as it promotes rote learning.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis also shows that shadow education is a theme that involves many authors and citations. These relationships become an This study also emphasizes that the role of government policies in drafting education regulations related to shadow education is very important for the development of shadow education [39]- [42].…”
Section: Three Fields Plot Analysis Of Shadow Educationmentioning
confidence: 92%